The Effect of Compensation on Container Driver Discipline: The Mediating Role of Work Motivation - Mochklas, Mocahamad; Silvia, Maulana Anifa; Iradawaty, Sofiah Nur; Hafidulloh, Hafidulloh (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2024)
Container drivers often face problems related to work discipline, including punctuality, performance, consistent attendance, and financial difficulties. These problems include on-time arrival, schedule efficiency, the effect of fatigue and stress on performance, disruption to attendance due to health factors, and financial difficulties that require company assistance through a good funding system. Container drivers in the export-import trade have a large contribution to the punctuality of delivery, therefore truck driver work discipline is the main factor that influences the productivity and performance of container drivers. Container drivers who work with full work discipline have a good impact on the development of transportation service companies, therefore this research aims to analyze the influence of compensation and work motivation on container driver discipline. This research uses quantitative methods, where the population in this study is PT container drivers. Multi Trans Surabaya. A total of 63 people met the criteria to become respondents in this research. The incoming data was processed using SEM_PLS. The results of this research are that compensation has a significant positive effect on the work discipline of container drivers, compensation has a significant positive effect on the work motivation of container drivers, work motivation has a significant positive effect on the work discipline of container drivers and work motivation mediates the effect of compensation on the work discipline of container drivers.